2018
DOI: 10.1093/nar/gky1158
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fluorescence imaging determines the absolute number of locked nucleic acid oligonucleotides needed for suppression of target gene expression

Abstract: Locked nucleic acid based antisense oligonucleotides (LNA-ASOs) can reach their intracellular RNA targets without delivery modules. Functional cellular uptake involves vesicular accumulation followed by translocation to the cytosol and nucleus. However, it is yet unknown how many LNA-ASO molecules need to be delivered to achieve target knock down. Here we show by quantitative fluorescence imaging combined with LNA-ASO microinjection into the cytosol or unassisted uptake that ∼105 molecules produce >50% knock d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 67 publications
3
31
0
Order By: Relevance
“…We also attempted knockdown of miR-71 using LNA anti-miR but neither phenotypic alterations nor changes in mRNA levels were observed although miR-71 levels were decreased as measured by RT-qPCR. One possible explanation for these results is that most LNA molecules were retained in endosomes [48] and were not able to interact with cytosolic miR-71. The LNA anti-miR retained in endosomes could have been released after cell lysis to form strong heteroduplex with the miRNA [49], which is characteristic of this type of oligonucleotides and often causes false results in RT-qPCR.…”
Section: Gene Id Annotationmentioning
confidence: 94%
“…We also attempted knockdown of miR-71 using LNA anti-miR but neither phenotypic alterations nor changes in mRNA levels were observed although miR-71 levels were decreased as measured by RT-qPCR. One possible explanation for these results is that most LNA molecules were retained in endosomes [48] and were not able to interact with cytosolic miR-71. The LNA anti-miR retained in endosomes could have been released after cell lysis to form strong heteroduplex with the miRNA [49], which is characteristic of this type of oligonucleotides and often causes false results in RT-qPCR.…”
Section: Gene Id Annotationmentioning
confidence: 94%
“…At present, most studies on intracellular presence and trafficking rely on covalent attachment of a fluorophore onto the oligonucleotide [38][39][40][41][42][43]. These studies involving fluorescently labeled oligonucleotides are beneficial to understanding the distribution, and some constructs mimic very well the situation of unconjugated AON [44]. However, chemically modified AONs will not, or cannot, act exactly in vitro and in vivo as the unconjugated AON, and some reports have shown that certain modifications or fluorescent tags alter the properties of an oligonucleotide significantly [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…As we were finishing this manuscript, an article was published in which the nuclear concentration needed for knockdown of the abundant long noncoding RNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) using locked nucleic acid (LNA) gapmers was determined (48). Approximately 100,000 LNA molecules were required for 50% knockdown of this transcript with a copy number of ;2500 per cell (based on literature values).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, areas that showed highly fluorescent spots from other focal planes than the nucleus were distinguished from those nuclei that had a homogeneous fluorescence distribution. For each of the 3 independent uptake experiments, between 57 and 103 nuclei were measured (untreated control [38][39][40][41][42][43][44][45][46][47][48]. A 1-way ANOVA was performed to test whether there was a treatment effect.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%